IMPLEMENTATION OF DEATH CERTIFICATE REPORTING POLICY IN SUKAGUMIWANG DISTRICT, INDRAMAYU REGENCY - Nurudin Siraj; Aghnia Dian Lestari; Yhonanda Harsono; Dimas Saputra (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
This study discusses the Implementation of Death Certificate Reporting Policy in Gedangan Village, Sukagumiwang District, Indramayu Regency. The implementation of making death certificate reports in Sukagumiwang District, Indramayu Regency is still not optimal. Researchers analyzed and answered problems in the implementation of making death certificate reports and the factors that hindered the implementation of policies for making death certificates reporting in Gedangan Village, Sukagumiwang District, Indramayu Regency. The author aims to describe the implementation of policies in Sukagumiwang District as policy implementers. The background for writing is because it strives to achieve goals. However, the facts on the ground that the implementation of the policy for making death certificate reports are still not optimal. This research includes qualitative research with in-depth interviews, direct observation and literature study. The field study was conducted through interviews with the Sukagumiwang sub-district head who is authorized to implement policies for making death certificate reporting. Literature studies are obtained through books and legislation. The results obtained from the research are that Sukagumiwang Subdistrict, Indramayu Regency is the implementer of policies, especially in making death certificates such as providing death certificate reporting services, coordinating and socializing with every village and community in Sukagumiwang District, Indramayu Regency, and other factors that influence policies such as communication, resources, disposition and bureaucratic structure.